Brightness-enhanced electroluminescence driven by triboelectric nanogenerators through permittivity manipulation and impedance matching. (July 2022) - Gu, Mingwei; Chen, Yunfeng; Gu, Shaoqiang; Wang, Can; Chen, Liguo; Shen, Hao; Chen, Guanyu; Sun, Xuhui; Huang, Haibo; Zhou, Yunlei; Wen, Zhen
Abstract: Triboelectric nanogenerator-driven electroluminescence (TDEL) that can convert human kinetic energy into visible light has attracted extensive attention in wearable electronics. However, the brightness is usually low due to the low electric field strength on the phosphors caused by impedance mismatch. In this work, a TDEL system with optimal brightness has been proposed by adjusting the dielectric constant of nanocomposite and matching impedance. The circuit model of the TDEL system is established and the voltage of the EL layer is predicted through simulation with an error below 4.7%. Finite element simulation is used to simulate the optimal field strength of phosphors under the dual effects of voltage drop and polarization enhancement of the EL layer caused by the increase of dielectric constant of nanocomposites. When the volume ratio of ZnS:Cu is 40% and the dielectric constant of the composite increases from 12 to 22.8, the optimal brightness value increases by 172%. Finally, a patterned TDEL system driven by walking or running to realize night alarm and information exchange is demonstrated. This study opens the window to improve the brightness of TDEL system through permittivity manipulation and impedance matching, which applies to different types of TENG, luminescent particles, and dielectric nanocomposites. Graphical Abstract: A triboelectric nanogenerator-driven electroluminescence system with optimal brightness has been proposed by adjusting the dielectric constant of nanocomposite and matching impedance with TENG. The equivalent circuit model of the system is constructed and voltage of EL layer can be predicted. The finite element simulation is used to simulate the best field strength of phosphors under the dual effects of voltage drop and polarization enhancement of EL layer caused by the increase of dielectric constant of nanocomposites in TDEL system. This study opens the window to improve the brightness of TDEL system through permittivity manipulation and impedance matching, which is applicable to different types of TENG, luminescent particles and dielectric nanocomposites. ga1 Highlights: Brightness-enhanced electroluminescence has been proposed by adjusting the dielectric constant and impedance matching. The equivalent circuit model of the system is constructed and voltage of EL layer can be predicted. Finite element simulation is used to simulate the best field strength of phosphors in TDEL system.